2007
DOI: 10.1038/oby.2007.357
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci for Regional Adiposity in Mouse Lines Divergently Selected for Food Intake

Abstract: Quantitative trait loci for regional adiposity in mouse lines divergently selected for food intake. Obesity. 2007;15:2994 -3004. Objective: Obesity is thought to result from an interaction between genotype and environment. Excessive adiposity is associated with a number of important comorbidities; however, the risk of obesity-related disease varies with the distribution of fat throughout the body. The aim of this study was to map quantitative trait loci (QTLs) associated with regional fat depots in mouse lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…A thrifty gene on Chromosome 14 defined by caloric efficiency was a dominant-acting genetic component of high-fat diet-induced obesity in a F2 intercross of C57BL/6 and 129S6/SvEv mice (Almind and Kahn, 2004). Finally, using a F2 intercross, QTL analyses of fat depots in mouse lines divergently selected for food intake revealed that Chromosomes 4 and 19 were associated with both white and brown adipose tissue depots, whereas Chromosome 9 was associated with only white adipose tissue depots (Rance et al, 2007). It would be of future interest to link underlying pharmacological control of fat intake with QTL analyses of highly-sensitive (e.g., SWR, DBA/2 ) and less-sensitive ( BALB/c ) strains.…”
Section: Discussionmentioning
confidence: 99%
“…A thrifty gene on Chromosome 14 defined by caloric efficiency was a dominant-acting genetic component of high-fat diet-induced obesity in a F2 intercross of C57BL/6 and 129S6/SvEv mice (Almind and Kahn, 2004). Finally, using a F2 intercross, QTL analyses of fat depots in mouse lines divergently selected for food intake revealed that Chromosomes 4 and 19 were associated with both white and brown adipose tissue depots, whereas Chromosome 9 was associated with only white adipose tissue depots (Rance et al, 2007). It would be of future interest to link underlying pharmacological control of fat intake with QTL analyses of highly-sensitive (e.g., SWR, DBA/2 ) and less-sensitive ( BALB/c ) strains.…”
Section: Discussionmentioning
confidence: 99%
“…It is recognized that sex  genotype as well as sex  genotype  environment interactions play a critical evolutionary role in producing and maintaining genetic variation (Mackay 2001). Several sex  QTL interactions have been reported, including those that influence tissue mass (Rance et al 2007), bone mineral density (Ishimori et al 2008), and pain responses (Mogil et al 1997). Given its magnitude and proximity to the MM locus, the triceps surae mass MMU11 QTL interaction with sex could prove beneficial for delineating the genetic architecture of MM.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in mice have identified quantitative trait loci (QTLs) that influence various obesity related traits. For example, QTLs have been identified for regional adiposity [6], diet induced obesity [7], resistance to diet induced obesity [8], juvenile obesity [9], obesity associated diseases [10,11] as well as lipid content in the liver [12]. …”
Section: Introductionmentioning
confidence: 99%
“…The dissection of fat depots [6], dual energy X-ray absorptiometry (DEXA) [13,14], or magnetic resonance imaging (MRI) [9,13] have been used to measure fat pad size and body fat distribution. Chromatographic techniques (gas chromatography, HPLC) [13], different biochemical reagent sets [8], or enzymatic assays [10] are used for metabolic profiling to obtain information about specific components such as cholesterol, triglycerides, glycerol and others.…”
Section: Introductionmentioning
confidence: 99%